Temperature, precipitation and sunshine across China, 1912‐51: A new daily instrumental dataset. (4th May 2020) - Png, Ivan P.L.; Chen, Yehning; Chu, Junhong; Feng, Yikang; Lin, Elaine Kuan‐Hui; Tseng, Wan‐ling
Abstract: This project compiled 463, 530 instrumental observations of daily temperature, precipitation and sunshine at up to 319 stations in China between 1912 and 1951. The principal sources are monthly reports of the Institute of Meteorology, Nanjing, observatories in Japanese‐occupied Manchuria, and the Japanese Army in North China. Gross errors, rounding errors and inhomogeneities are identified. The new dataset is temporally and spatially consistent with existing datasets of monthly temperature, but reports higher precipitation and sunshine. Abstract : Left: Monthly Meteorological Bulletin (Institute of Meteorology, Nanjing), February 1929. Right: North China Meteorological Monthly (Japanese Army), February 1939.